ANALISIS PERILAKU EKONOMI RUMAHTANGGA PETANI USAHA TERNAK SAPI-KELAPA DALAM MENGHADAPI BIAYA TRANSAKSI DI KABUPATEN BOLAANG MONGONDOW - Femi Hadidjah Elly (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2009)
Analysis of The Economic Behavior of Coconut-Cattle Farmer Households in Facing The Transaction Cost in Bolaang Mongondow. A number of households in Bolaang Mongondow raise cattle integrated in their coconut plants. A farmer household farmer as an analysis unit plays the roles of a producer, a consumer and a labor provider. The phenomenon faced is the existence of transaction costs during the trades of cattle and copra. The objective of the study was to analyze the factors influencing the input, output, farmer household income and expenditures in Bolaang Mongondow related to the transaction cost. The research method carried out was the survey method. The 233 household respondents were determined by using simple random sampling. The analysis method used simultaneous equations model with two SLS. The results show that higher transactions costs cause the decrease on the household economic activities especially in the production side and labor allocation for the cattle and coconut farm operations. The intermediary cost as a cost component in cattle transaction is influenced by the cattle price, cattle selling and the distance to the market. The transportation cost as a cost component in copra selling is affected by the copra price, the use of cattle labors to carry copra.Key words : Transaction cost, household economics, coconut-cattle farming systemABSTRAKSebagian rumahtangga di Bolaang Mongondow memelihara ternak sapi diintegrasikan dengan tanaman kelapa. Rumahtangga petani peternak sapi sebagai suatu unit analisis selain berperan sebagai produsen, konsumen juga sangat berperan sebagai penyedia tenaga kerja. Fenomena yang dihadapi adalah adanya biaya transaksi dalam penjualan ternak sapi dan penjualan kopra. Penelitian ini bertujuan menganalisis faktor-faktor yang mempengaruhi penggunaan input, produksi, pendapatan dan pengeluaran rumahtangga petani peternak sapi di Bolaang Mongondow berkaitan dengan biaya transaksi. Metode penelitian yang dilakukan adalah metode survai. Jumlah responden 233 rumahtangga yang ditentukan secara simple random sampling. Metode analisis menggunakan 2SLS. Hasil penelitian menunjukkan biaya transaksi yang semakin tinggi mengakibatkan penurunan aktivitas ekonomi rumahtangga terutama sisi produksi dan alokasi tenaga kerja pada usahaternak sapi maupun usahakebun kelapa. Biaya perantara sebagai komponen biaya transaksi penjualan sapi dipengaruhi harga ternak sapi, penjualan sapi dan jarak pasar. Biaya transpor sebagai komponen biaya transaksi penjualan kopra dipengaruhi harga kopra dan penggunaan tenaga kerja ternak sapi untuk angkut kopra.Kata kunci : Rumahtangga, biaya transaksi, ternak sapi, kelapa